Does Digital Literacy Influence SDL Performance of Pre-Service Educators? - Rohmah, Lailati; Mustadi, Ali; Pujiastuti, Pratiwi; Wijayanti, Inggit Dyaning (Universitas Pendidikan Ganesha, 2022)
The development of technology is directly proportional to the progress of education. It requires students to continue to improve their learning capacity, including using technology to support learning. The ability of students to use digital platforms is one of the skills students must have to be able to face the new era of the 21st century. This research aims to analyze prospective teacher students' digital literacy and its effect on independent learning ability to face 21st-century skills. This research uses a quantitative approach with a correlational type. The population is 84 active students. Data collection was carried out by conducting surveys and distributing questionnaires. Instruments used in digital literacy questionnaires and self-directed learning. Data analysis technique using simple linear regression analysis. This study found that the correlation between the variables was positive but included in the low category. Conversely, the indicators for each variable have a good score or value with the ability to use digital technology of 76.12% and an evaluation of 62.97%. It is concluded that the higher a person's digital literacy, the higher the strength of a person's independent learning ability. Learning to do self-management is significantly related to information literacy skills, namely analyzing information. Differences in independence result in differences in the ability to absorb the material and use technology appropriately.